Successful weight loss maintainers use health‐tracking smartphone applications more than a nationally representative sample: comparison of the National Weight Control Registry to Pew Tracking for Health. (27th March 2017) - Goldstein, C. M.; Thomas, J. G.; Wing, R. R.; Bond, D. S.
Summary: Objective: The objective of this paper is to evaluate successful weight loss maintainers' use of self‐monitoring technology. Methods: National Weight Control Registry (NWCR) participants, who maintained a ≥13.6 kg weight loss for ≥1 year, completed an online survey about self‐monitoring technology use. The NWCR sample ( n  = 794) was compared with a demographically similar subsample of 833 individuals answering the same questions in the Pew Tracking for Health Survey. Results: The NWCR had higher rates of tracking weight, diet or exercise using any modality (92.8% vs. 71.3%), on a regular basis (67.4% vs. 41.3%), and frequency of updating records, compared with Pew ( p s < .01). Smartphone ownership was higher in NWCR participants (80.2% vs. 52.8%, p  < .001), and NWCR smartphone owners had 23.1 times greater odds for using diet, food or calorie counter apps (58.9% vs. 5.9%) and 15.5 times greater odds for using weight monitoring apps (31.7% vs. 3.0%; all p s < .01). Pew respondents more often changed their behaviour based on their tracking data ( p s < .01). Conclusion: Use of self‐monitoring technology is common in weight loss maintainers: more so than in a nationally representative sample. However, the national sample more often changed their behaviour based on tracking data, perhaps suggesting that weight loss maintainers could derive additional benefit from technology they are already using.